An extensive numerical survey of the correlation between outflow dynamics and accretion disk magnetization - Stepanovs, Deniss; Fendt, Christian (The astrophysical journal, 2016)
We investigate the accretion-ejection process of jets from magnetized accretion disks. We apply a novel approach to the jet-launching problem in order to obtain correlations between the physical properties of the jet and the underlying disk. We extend and confirm the previous works of Tzeferacos et al. and Murphy et al. by scanning a large parameter range for the disk magnetization, . We disentangle the disk magnetization at the foot point of the outflow as the main parameter that governs the properties of the outflow. We show how the four jet integrals known from steady-state MHD are correlated to the disk magnetization at the jet foot point. This agrees with the usual findings of the steady-state theory, however, here we obtain these correlations from time-dependent simulations that include the dynamical evolution of the disk in the treatment. In particular, we obtain robust correlations between the local disk magnetization and (i) the outflow velocity, (ii) the jet mass loading, (iii) the jet angular momentum, and (iv) the local mass accretion rate. Essentially, we find that strongly magnetized disks launch more energetic and faster jets and, due to a larger Alfvén lever arm, these jets extract more angular momentum from the underlying disk. These kinds of disk-jet systems have, however, a smaller mass loading parameter and a lower mass ejection-accretion ratio. The jets are launched at the disk surface where the magnetization is . The magnetization rapidly increases vertically providing the energy reservoir for subsequent jet acceleration. We find indications of a critical disk magnetization that separates the regimes of magneto-centrifugally driven and magnetic pressure-driven jets.
Gesehen am 15.05.2020